2011
DOI: 10.1111/j.1440-1843.2011.02005.x
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm and peripheral muscle thickness on ultrasound: Intra‐rater reliability and variability of a methodology using non‐standard recumbent positions

Abstract: This ultrasound technique has good reliability in recumbent positions, making it useful for application to clinical populations when the erect posture is not practical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 32 publications
(71 reference statements)
4
78
0
5
Order By: Relevance
“…Other studies of reference values in smaller populations found mean diaphragm thickness to be 0.16-0.27 cm. [10][11][12] These differences may be secondary to the ethnic background of subjects or differences in ultrasound devices or technique.…”
Section: -213mentioning
confidence: 99%
“…Other studies of reference values in smaller populations found mean diaphragm thickness to be 0.16-0.27 cm. [10][11][12] These differences may be secondary to the ethnic background of subjects or differences in ultrasound devices or technique.…”
Section: -213mentioning
confidence: 99%
“…It can be performed at the bedside, is noninvasive, is inexpensive, shows good interobserver and intraobserver reliability [10,11], and is readily available in most hospitals [12]. Reliability for the measurement of quadriceps muscle thickness, and echogenicity have been demonstrated in individuals with critical illness in several recent studies [13][14][15].…”
Section: Introductionmentioning
confidence: 97%
“…During contraction, this area shortens and thickens as a result of muscle contraction [58]. The physical dimensions of the appositional area and the configuration and motion of the dome of the diaphragm can be quantified by US as reported by several authors [22,23,24,26,27,30,32,41,49,50,60,61,62,63,64,65,66] (fig. 1; table 2).…”
Section: Review Findingsmentioning
confidence: 99%